First-in-man use of an Indian-made balloon-expandable covered Zephyr stent and intermediate-term follow-up - Pramod Sagar; Thejaswi Puthiyedath; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2023)
Covered stent is used in large-vessel angioplasty in anticipation of vessel wall injury. Apart from aortic coarctation, they are also used in dysfunctional right ventricular outflow conduits and find a recent role in transcatheter sinus venosus defect closure. Different methods of covering stents include glue fixation, sutureless lamination, sandwich, and sintering lamination. Covered Zephyr (Sahajanand laser technology limited, Gandhinagar, India) is a new Indian-made expanded polytetrafluoroethylene-covered balloon expandable cobalt-chromium stent. Its unique C and S links prevent foreshortening. We report the first-in-man use of this new stent in severe discrete postsubclavian coarctation of aorta and its short-term follow-up imaging.